(untitled) (Derna Academy Journal for Applied Sciences, 2025)
Background: Door handles represent frequently touched surfaces that may act as vehicles for microbial transmission. In regions with high temperature and strong sunlight, the survival of microorganisms on such surfaces can be influenced, yet data from community settings remain limited. Methods: This cross-sectional study examined 25 external door handles from retail shops in Qasr Bin Ghashir, Tripoli (15 food stores and 10 butcheries). Sterile swabs were collected and inoculated onto nutrient, blood, and MacConkey agar. Plates were incubated at 37 °C for 24–48 hours, and colony-forming units (CFU) were categorized into <10, 10–100, 101–1000, and >1000. Isolates were identified by morphology, Gram stain, and standard biochemical tests. Results: The predominant CFU category was 10–100 (40%). Bacillus spp. (35%) and coagulase-negative staphylococci (27%) were the most frequent isolates, followed by Micrococcus luteus (12%). Pathogenic species were also detected, including Staphylococcus aureus (6%), Enterococcus faecalis (15%), Escherichia coli (3%), and Klebsiella pneumoniae (3%), with butcheries yielding more pathogens. Heavy contamination (>1000 CFU) was observed on 16% of handles. Conclusion: Most door handles in this setting carried low-to-moderate bacterial loads, dominated by environmental and skin flora, though occasional pathogens were recovered. These findings emphasize the importance of routine disinfection of frequently touched surfaces and maintaining proper hand hygiene in community environments.